Out of control: A self-control perspective on the link between surface acting and abusive supervision - Yam, Kai Chi; Fehr, Ryan; Keng-Highberger, Fong T; Klotz, Anthony C; Reynolds, Scott J (Journal of applied psychology, 2016)
In this study, we examined how leaders' customer interactions influence their tendency to abuse their followers. Specifically, we drew from ego-depletion theory to suggest that surface acting during customer interactions depletes leaders of their self-control resources, resulting in elevated levels of abusive supervision. Furthermore, we hypothesized that the effect of surface acting on abusive supervision is moderated by leaders' trait self-control, such that leaders with high trait self-control will be less affected by the depleting effects of surface acting than their peers. Results from a multiwave, multisource leader-follower dyad study in the service and sales industries provided support for our hypotheses. This research contributes to several literatures, particularly to an emerging area of study--the antecedents of leaders' abusive behaviors.